Elucidating the Rate‐Limiting Processes in High‐Temperature Sodium‐Metal Chloride Batteries. Issue 17 (11th April 2022) - Landmann, Daniel; Svaluto‐Ferro, Enea; Heinz, Meike V. F.; Schmutz, Patrik; Battaglia, Corsin
Abstract: Sodium‐metal chloride batteries are considered a sustainable and safe alternative to lithium‐ion batteries for large‐scale stationary electricity storage, but exhibit disadvantages in rate capability. Several studies identify metal‐ion migration through the metal chloride conversion layer on the positive electrode as the rate‐limiting step, limiting charge and discharge rates in sodium‐metal chloride batteries. Here the authors present electrochemical nickel and iron chlorination with planar model electrodes in molten sodium tetrachloroaluminate electrolyte at 300 °C. It is discovered that, instead of metal‐ion migration through the metal chloride conversion layer, it is metal‐ion diffusion in sodium tetrachloroaluminate which limits chlorination of both the nickel and iron electrodes. Upon charge, chlorination of the nickel electrode proceeds via uniform oxidation of nickel and the formation of NiCl2 platelets on the surface of the electrode. In contrast, the oxidation of the iron electrodes proceeds via localized corrosion attacks, resulting in nonuniform iron oxidation and pulverization of the iron electrode. The transition from planar model electrodes to porous high‐capacity electrodes, where sodium‐ion migration along the tortuous path in the porous electrode can become rate limiting, is further discussed. These mechanistic insights are important for the design of competitive next‐generation sodium‐metal chloride batteries with improved rate performance. Abstract : Electrochemical de‐/chlorination of nickel and iron model electrodes is studied in molten sodium tetrachloroaluminate at 300 °C in a planar cell geometry. While the transport of metal‐ions through the melt emerges as rate‐limiting process in both cases, nickel and iron electrodes exhibit different chlorination behaviors. This results in dissimilar rate capabilities and cycle life.